Analisis Penjadwalan Produksi Dengan Metode Campbell Dudek Smith (CDS), PT. ISM TBK. Divisi Bogasari Flour Mills Jakarta - Purwati Purwati; Santika Sari (OPSI, 2020)
Bogasari is one of the largest wheat flour companies in Indonesia, besides wheat flour also produces a byproduct namely pasta, pellet, and livestock food. As a large company that produces many products need to do production scheduling so that the production time and product quantity produced reach the maximum. To avoid the extension of the production completion time that can ultimately lower the production quantity, one of the strategies that the company can do is by scheduling and allocating the company's resources. The selection of the right scheduling method needs to be done so that the company can have a decision in production scheduling that results in a minimum production completion time and the demand can be fulfilled on time. The methods used are CDS (Campbell Dudek Smith), SPT (Shortest Processing Time), LPT (Longest Processing Time), EDD (Earliest Due Date), and FCFS (First Come First Served). From the results of the research conducted the best scheduling method is the CDS with a makespan of 2,576,807.5 minutes and a flowtime of 21,665,932 minutes